Romanian Literature in British Translation Prizes - Antony Hoyte-West (Translation Studies: Theory and Practice)
As a component of a larger project on translation awards, this article examines the presence of literary works originally written in Romanian in recent iterations of four prominent British prizes for literary translation: the EBRD Literature Prize, the Warwick Prize for Women in Translation, the International Booker Prize, and the Oxford-Weidenfeld Prize. Noting that Romanian is the official language in both Romania and Moldova, the article opens by outlining the necessary linguistic, literary, and sociohistorical background, before moving to the British context by presenting the framework and scope regarding the four selected literary translation awards. After scrutinising the longlists, shortlists, and winners of the awards to determine the presence of translated Romanian-language works, the analysis is discussed and then briefly compared with some of the project’s other findings.